2019
DOI: 10.26480/bda.01.2019.21.25
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Import, Use, Consumption and Residue Status Among Food Crops in Nepal: A Review

Abstract: Insubstantial options for chemical pest management compelled farmers to use synthetic pesticides against crop insect pests that created vicious circle of increasing high-dose-pesticides applications in agriculture sector. The study was carried out to understand prevailing situation of pesticides uses and their state regulation status. Secondary data were obtained from Plant Protection Division, Plant Management and Registration Division, and FAOSTAT for drawing inferences and trend analysis. Chemical pest mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…It has been estimated that the pesticide use pattern in Nepal is increasing by 10-20% every year [11]. e substantial increase in pesticide consumption is due to the dependency of agricultural crops and their productivity on synthetic pesticides [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that the pesticide use pattern in Nepal is increasing by 10-20% every year [11]. e substantial increase in pesticide consumption is due to the dependency of agricultural crops and their productivity on synthetic pesticides [12].…”
Section: Introductionmentioning
confidence: 99%
“…In last years, pesticide use has considerably increased in China [ 12 , 13 , 14 ], corresponding to over 60% of the pesticide applied worldwide [ 11 ]. Resistance evolution is a major challenge associated with pesticides among other challenges for health and the environment [ 15 , 16 ]. Spodoptera litura has been shown to be resistant to a range of chemicals, and is ranked among the top ten most resistant insect pests of the world, with 638 reported case of resistance against 39 active ingredients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Nepal, no extensive studies on pesticide residues in fruits, grains and vegetables has been carried out. Threat from pesticide residue is blooming, with the increasing use of pesticides on vegetables [31]. Previous studies have shown pesticide residues on vegetables [32][33][34].…”
Section: Assessment Of Neurotoxic Pesticides Residues In Fruits and V...mentioning
confidence: 99%